Experiential approach to strategy formulation - SMITH, Richard Raymond (Institutional Knowledge at Singapore Management University, 2020)
While strategy formulation is a topic of active research by strategy scholars, the methods for teaching strategy formulation are often left to conceptual frameworks and generic toolset in the business school classroom. Ultimately, strategy formulation is about taking action and one of the best ways to teach it is through physical application via the experiential approach. This chapter discusses our experience in teaching strategy formulation through the experiential approach. We share the background associated with teaching strategy and experiential approaches, provide an overview of the concepts used to making teaching in an experiential format most effective, share a proven process for teaching in this method, and consider several discussion questions. Our goal is to share our experiences, challenges and insights as we experimented with and taught business practicum courses, in the hope that readers interested in teaching strategic formulation using the experiential approach may benefit from it.​​​​​​​